Pus organisms - Wakefield, Orin Russell (My University, 1904)
Introduction: To the casual observer the term, pus organism, means little more than a boil with a yellow top,a red swelling, an incision and the gushing out of a yellowish pus matter,or a sensation of pain may suggest itself. But to the scientific mind,afield of intense interest is spread out before it and in a moment beholds the organism as a living microscopic plant,producing suppuration in the living animal tissue,sees it in the soil, in the water,the air,milk,and in the vegetable and,animal tissue. Any organism which,by its physical presence or activity in chemical elaboration, acting on the living animal tissue, producing tissue necrosis,inflammation,suppuration, and finally,the formation of pus,may be termed, puss organisms. They occur widely distributed in the external world, and have been found in milk, in wash-water and in waste water, as well as in the air of opperating-rooms and sick-rooms Giving attention to pus organisms in the animal tissue, there are four aspects from which they may be considered.Namely,conditions favoring infection,their effects and how caused, their removal from infected parts, and their importance in surgery.
Citation: Wakefield, Orin Russell. Pus organisms. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Pus; Bacteria; Infections; Theses